2022
DOI: 10.1155/2022/3838928
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Emergency Specialist Nursing Combined with Green Channel Mode in Patients with Limb Amputation

Abstract: Background. The treatment of limb amputation is always a challenge to emergency medical staff. The success of replantation of severed limbs requires not only emergency professional nursing measures but also rapid transport against time. We that found emergency specialist nursing combined with green channel mode can effectively improve the success rate of amputated limb replantation surgery. Methods. From September 2017 to August 2020, the medical records of 80 patients with severed limb replantation treated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Based on this view, previous studies suggested that targeted psychological intervention combined with planned pain care could improve pain after AIO surgery [5]. Some studies also indicate that rapid rehabilitation nursing can promote postoperative recovery [6]. Previous literature studies have shown that humanized nursing can efectively reduce the perioperative adverse reactions of AIO patients and has application value [7].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this view, previous studies suggested that targeted psychological intervention combined with planned pain care could improve pain after AIO surgery [5]. Some studies also indicate that rapid rehabilitation nursing can promote postoperative recovery [6]. Previous literature studies have shown that humanized nursing can efectively reduce the perioperative adverse reactions of AIO patients and has application value [7].…”
Section: Introductionmentioning
confidence: 99%
“…The second leading external cause of unintentional injury in Central China was EIMF, which was influenced by various factors, such as socio-economic status, environmental conditions, population characteristics, and behavioral habits ( 37 ). In our study, EIMF was more prevalent among children aged 1–6 years, and more frequent in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the implementation of the standard fast medical procedures is patient-centered, by carrying out information linkage between multiple departments, they can communicate and discuss the patient's situation in a timely manner, clearly divide the work, cooperate with each other, do their own work in an orderly manner, then develop the best treatment plan for the patient, and ensure good treatment equipment conditions, so that the patient's treatment process is systematic and continuous, thus ensuring the success rate of patient treatment [ 11 , 12 ]. The green channel approach can make up for the defects of the traditional emergency route, remove the prehospital obstacles as much as possible, and ensure that the patients are quickly admitted to the emergency room and receive treatment in the shortest time, and its rapidity can improve the treatment efficiency [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%